Anti‐inflammatory and macrophage polarization effects of Cranberry Proanthocyanidins (PACs) for periodontal and peri‐implant disease therapy. (18th June 2020) - Galarraga‐Vinueza, Maria Elisa; Dohle, Eva; Ramanauskaite, Ausra; Al‐Maawi, Sara; Obreja, Karina; Magini, Ricardo; Sader, Robert; Ghanaati, Shahram; Schwarz, Frank
Abstract: Background and Objective: Macrophages' cytokine expression and polarization play a substantial role in the host's "destructive" inflammatory response to periodontal and peri‐implant pathogens. This study aimed to evaluate cell viability, anti‐inflammatory activity, and macrophage polarization properties of different cranberry concentrates. Methods: THP‐1 cells (monocytic line) were treated with phorbol myristic acid to induce macrophage differentiation. Human gingival fibroblasts (HFIB‐G cell line), osteosarcoma‐derived osteoblasts (SAOS‐2 cell line), and induced macrophages were treated with cranberry concentrates at 25, 50, and 100 µg/mL for 120 seconds, 1 hour and 24 hours. Untreated cells at the same time points served as controls. For anti‐inflammatory analysis, induced macrophages exposed to cranberry concentrates (A‐type PACs) were stimulated with lipopolysaccharides (LPS) derived from E coli for 24 hours. Cell viability, interleukin (IL)‐8, IL‐1 ß, IL‐6, and IL‐10 expression of LPS‐stimulated macrophages, and macrophage polarization markers were evaluated through determination of live‐cell protease activity, enzyme‐linked immunosorbent assay, and immunofluorescence staining semi‐quantification. Results: Cranberry concentrates (A‐type PACs) did not reduce HGF, SAOS‐2, and macrophage viability after 24 hours of exposure. Pro‐inflammatory cytokine expression (ie IL‐8 and IL‐6) was downregulated in LPS‐stimulated macrophages by cranberry concentrates at 50 and 100 µg/mL. Anti‐inflammatory IL‐10 expression was significantly upregulated in LPS‐stimulated macrophages by cranberry concentrates at 100 µg/mL after 24 hours of exposure. M1 polarization significantly decreased when LPS‐stimulated macrophages were exposed to cranberry concentrates. High levels of positive M1 macrophages were present in all untreated control groups. M2 polarization significantly increased at all LPS‐stimulated macrophages exposed to cranberry concentrates for 1 and 24 hours. Conclusion: Cranberry‐derived proanthocyanidins may have the potential to act as an anti‐inflammatory component in the therapy of periodontal and peri‐implant diseases.